CEO Self-Monitoring and Corporate Entrepreneurship: A Moderated Mediation Model of the CEO-TMT Interface. (November 2022) - Chen, Jianhong; Simsek, Zeki; Liao, Yi; Kwan, Ho Kwong
Focusing on the interface between CEOs and top management teams (TMTs), we argue that CEO self-monitoring positively impacts a firm's pursuit of corporate entrepreneurship through the intervening role of TMT behavioral integration. We additionally argue that the impact becomes stronger as the firm's discretionary slack decreases because decreased slack creates an organizational context more favorable to the influences of both CEO self-monitoring and TMT behavioral integration. Results based on multisource (CEOs and TMTs) and multiwave data from 110 firms support the model and associated hypotheses.